Impact of student-teacher relationships on Bangladeshi students in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University, Wellington Campus, New Zealand / - Chowdhury, Nazneen Afsana (Massey University, 2005)
This study explores the impact of overseas students' relationships with their teachers on them. Nowadays the universities worldwide, especially the universities in the western world are increasingly having large numbers of overseas students in their tertiary education sectors. When students go abroad for higher study purpose they confront manifold problems and strains in their academic endeavours as well as in their personal and emotional lives, through facing different academic systems, different language and teachers and peers of different cultures. One major concern directly related to their academic success and overall wellbeing is their interactions and relationships with their teachers who, obviously, are from diverse cultures. Although the literature and various research reports have already focused on the problems faced by overseas students and their teachers in teaching-learning activities, there is little research available on how overseas students perceive their relationships with their teachers and impact of these on them. For this research eight Bangladeshi people with tertiary study experience in New Zealand were interviewed about their study experiences including their views regarding their relationships with their teachers, their feelings and realizations about the impacts of those relationships on them and about the overall importance of this relationship for an overseas student. The findings of this research emphasize that an overseas student's relationship with teacher carries great significance in reducing her/his troubles and stress and offering mental and emotional support to enhance academic efforts and achievement. This study recommends good understanding and sincere effort by both an overseas student and her/his teacher to know each other and increase cultural sharing to form a promising relationship.
Keywords: New Zealand; Teacher-student relationships -- Case studies; Bangladeshi students; Education (Higher); Minority college students